1996
DOI: 10.1111/j.1558-5646.1996.tb04481.x
|View full text |Cite
|
Sign up to set email alerts
|

NONRANDOM GENOTYPIC ASSOCIATIONS IN A LEGUME— BRADYRHIZOBIUM MUTUALISM

Abstract: Abstract.-Genetically divergent lineages often coexist within populations of the annual legume Amphicarpaea braeteata. At one site dominated by two such lineages (termed biotypes "C" and "S"), isolates of root-nodule bacteria (Bradyrhizobium sp.) were sampled from both hosts and analyzed by enzyme electrophoresis. Symbiont populations on the two plant biotypes were highly distinct. Out of 15 bacterial multilocus genotypes detected (among 51 isolates analyzed), only one was shared in common by the two plant bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 38 publications
(63 reference statements)
2
13
0
Order By: Relevance
“…In cases where a site was represented in more than one experiment (Table 1), different parents furnished seeds in each experiment. In a previous study of one site, symbiotic phenotypes were found to be highly consistent for different plant families in a given lineage (Spoerke et al 1996), which is not surprising in view of the limited withinlineage genetic diversity in local A. bracteata populations (Parker 1988(Parker , 1991.…”
Section: Sampling Of Plants and Bacteriamentioning
confidence: 66%
See 3 more Smart Citations
“…In cases where a site was represented in more than one experiment (Table 1), different parents furnished seeds in each experiment. In a previous study of one site, symbiotic phenotypes were found to be highly consistent for different plant families in a given lineage (Spoerke et al 1996), which is not surprising in view of the limited withinlineage genetic diversity in local A. bracteata populations (Parker 1988(Parker , 1991.…”
Section: Sampling Of Plants and Bacteriamentioning
confidence: 66%
“…Because reproduction occurs predominantly with obligately self-fertilized cleistogamous flowers, A. bracteata populations tend to be highly inbred (Parker 1988). Root nodule bacteria associated with A. bracteata are in the genus Bradyrhizobium, but appear to be distinct from the two species of Bradyrhizobium described to date (Spoerke et al 1996). Direct hereditary transmission of symbionts from parent plants to their offspring does not occur in the legume-rhizobial mutualism (Sprent and de Faria 1988).…”
Section: Study Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Support for this proposition was provided by our finding that A. bracteata and D. canadense were associated with distinct core, and to some extent, symbiotic gene lineages of soybean-nodulating bacteria. Moreover, Spoerke et al (1996) reported that distinct sub-populations of A. bracteata in a natural woodland environment were associated with different lineages of Bradyrhizobium defined on the basis of enzyme electrophoresis. Further investigation is obviously needed to elucidate the role of native legume biogeography (at local and regional scales) with regard to the spatial structuring of Bradyrhizobium populations associated with crop legumes.…”
Section: Discussionmentioning
confidence: 99%